Load Cell Technology In The Rice Holding Capacity Monitoring System At MKP Rice Milling In The Malind District - Jarot Budiasto; Stanley HD Loppies; Hebrian S. Pandera (Jurnal Info Sains : Informatika dan Sains, 2024)
Region District Malind, Merauke has a total amount resident as much ± 20,125soul. The majority of the population makes a living as farmers. The rice farmers' post-harvest food is supported by rice milling technology in the area. There are 14 rice mills, 1 of which is registered as a Rice Procurement Working Partner (MKP) with Perum Bulog. The system of absorbing farmers' rice by MKP mills is carried out only if Perum Bulog requires a supply of rice for Civil Servant (ASN) rations, social assistance, and supply rice to another region (move regional). System absorption like This felt impact to para farmer, that is to its height lost results postharvest farmer. Besides That current MKP milling This Also Not yet supported with use monitoring technology facilitate para farmer For obtain information related condition warehouse milling updated. Obstacles the can resolved with utilise technology LoadCell or A device hard on technology digital scales. Planning this monitoring system done use prototyping methods, ie build A design digital scales as well website application as a media for presenting data and information to user like farmer And party milling. As for results obtained on study This ie A innovation new in the transaction process on milling, like message service grinding, condition monitoring room accommodate grain And rice on warehouse milling for para farmer as well as report results absorb between party milling And Corporation Logistics Bureau as effort maximize handling results postharvest on area the.